FACTORS ASSOCIATED WITH HIV TESTING AMONG UNDERGRADUATE STUDENTS OF LIRA UNIVERSITY, A CROSS-SECTIONAL STUDY. - Tukamushaba , Angellah; Musinguzi, Marvin; Khanakwa, Voni; Ogang, Akullu Immaculate; Modi , Derick; Kasaija, Deo (SJ Insights, 2025)
Background HIV testing is a crucial starting point for the prevention, early diagnosis, and treatment of HIV. Therefore, the study assessed the factors associated with HIV testing among undergraduate students of Lira University. Methods A cross-sectional study was carried out among 327 undergraduate students of Lira University located in Lira district, Northern Uganda. Ethical approval to carry out the research was requested from the Research Ethics Committee of Lira University. A stratified simple random sampling was used to select the respondents proportionate to each size of the strata representing each faculty. Data was then collected using self-administered questionnaires, and data analysis was done using SPSS version 20. Results On the socio-demographic characteristics, the total number of males was 164(50.2%) and females was 163(49.8%). The majority of the respondents were in the age category (20-25), the mean age was 23.56, majority of the participants were single 177(81.8%). HIV testing among Lira University students was significantly influenced by HIV knowledge (73.4% knowledgeable, cOR: 1.27–3.73, p=0.005), sexual partnerships (two or more partners, cOR: 1.96–9.87, p=0.001), family encouragement (cOR: 1.27–3.73, p=0.005), awareness of university HIV testing services (cOR: 1.16–4.19, p=0.016), peer discussions (cOR: 1.06–3.66, p=0.033), and radio information (cOR: 1.19–4.14, p=0.013). Conclusion HIV testing among the participants was influenced by sex with more females having tested than males, being married, having two or more sexual partners and ever talking to the male/female guardian about HIV. Recommendations Developing policies that mandate regular HIV testing for all students entering higher education institutions can help ensure that a larger proportion of the student population is tested regularly.